(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Determination of the project competence of a teacher of foreign languages determines its structure, presents a model of its formation, and highlights the criteria for assessing the level of formation of this competence. Particular attention should be paid to practical tasks that prepare future teachers for the organization of project activities in the Russian language. It is necessary to reveal the importance of the formation of the project competence of the future teacher in the context of the introduction of new educational standards and consider the content and structure of this competence.